Hubungan Pola Asuh Pengasuh terhadap Perkembangan Motorik Halus Anak Usia Dini di Tempat Penitipan Anak - Nurhasana J. Monomo; Agiska Katili; Cika Aprilia Kuku; Siti Afrianti Asdik Labedi; Siti Nur Afni Kantoli (Institut Nalanda, 2025)
This study examines the effect of caregiver parenting styles on the fine motor development of early childhood in daycare environments through a quantitative approach with a correlational design. The analysis focuses on key dimensions of caregiving, namely responsiveness, consistency, and the provision of stimulating support, and their relationship with children’s fine motor abilities, including threading, cutting, pasting, and visual–motor coordination. The results reveal a strong positive association between the quality of caregiver parenting and the level of fine motor development in children. Regression analysis further confirms that caregiver parenting quality serves as a significant predictor of improvements in fine motor skills. In addition, several supporting factors, such as a conducive physical environment, an appropriate caregiver-to-child ratio, and well-designed stimulation programs, were found to strengthen the impact of caregiving practices in daycare settings. These findings emphasize the importance of enhancing caregiver competencies and developing effective caregiving systems to support optimal and sustainable fine motor development in early childhood.